2019
DOI: 10.1177/0004563219882042
|View full text |Cite
|
Sign up to set email alerts
|

Role of sFlt-1 and PlGF in the screening of small-for-gestational age neonates during pregnancy: A systematic review

Abstract: Background Fetal growth restriction, i.e. the restriction of genetically predetermined growth potential due to placental dysfunction, is a major cause of neonatal morbidity and mortality. The consequences of inadequate fetal growth can be life-long, but the risks can be reduced substantially if the condition is identified prenatally. Currently, screening strategies are based on ultrasound detection of a small-for-gestational age fetus and do not take into account the underlying vascular pathology in the placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…In this case, when we observe an increased expression of CX3CL1/CX3CR1 in placenta and corresponding restrained development of placental vessels, we suggest that the increase in CX3CL1 synthesis is rather the consequence of low angiogenesis in a kind of negative feedback after TNF-α stimulation. The interesting question is the correlation between Doppler parameters and CX3CL1 levels as there is a potential role of CX3CL1 to be another biomarker for clinical decisions, when used together with other biomarkers and clinical data [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, when we observe an increased expression of CX3CL1/CX3CR1 in placenta and corresponding restrained development of placental vessels, we suggest that the increase in CX3CL1 synthesis is rather the consequence of low angiogenesis in a kind of negative feedback after TNF-α stimulation. The interesting question is the correlation between Doppler parameters and CX3CL1 levels as there is a potential role of CX3CL1 to be another biomarker for clinical decisions, when used together with other biomarkers and clinical data [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the PROGNOSIS study showed that patients with an elevated sFlt1/PlGF ratio, but who did not develop preeclampsia, were at greater risk of giving birth to a growth-restricted baby [7]. These data, found in several smaller studies, were recently summarised in a systematic review [23]. Its findings, given the irreducible variety in design and methodology of the studies it reviews, do not allow the ratio to be recommended in current clinical practice as a reliable predictor of IUGR.…”
Section: Other Applications Of the Sflt1/plgf Ratiomentioning
confidence: 95%
“…Of note, despite being different animal models, the hyperoxia and intrauterine infection exposure resulted similarly in growth restriction. Indeed, growth restriction is a potent risk factor for BPD as the associated increase in sFlt-1 (soluble FMS-like tyrosine kinase-1) ( 6 ) has a negative impact on growth factors such as VEGF, a mediator that regulates vascular growth closely linked to the alveolarization process ( 7 ). As shown by Ruan et al , the effects of oxygen toxicity resulted in increased pulmonary vascular permeability, likely from endothelial damage, and reduced Twist1 that may potentially modify VEGF as well.…”
Section: Bronchopulmonary Dysplasiamentioning
confidence: 99%